434PPneumonitis induced antineoplastic agents: Mortality and risk factors in 129 consecutive cases. (24th November 2019) - Kaku, S; Horinouchi, H; Watanabe, H; Tamura, K; Okusaka, T; Boku, N; Yamazaki, N; Ohe, Y; Kusumoto, M
Abstract: Background: Although many reports classify drug-induced pneumonitis based on the tumour type or drug category, mortality of drug-induced pneumonitis across tumour types or drug categories at high-volume cancer centres are rarely reported. Methods: From January 2014 to December 2018, we reviewed patients who experienced drug-induced pneumonitis requiring hospitalization. We collected the patient's background, clinical and radiological features, and outcome of treatment for drug-induced pneumonitis. To evaluate the risk factors of death from drug-induced pneumonitis, we conducted a multivariate analysis of the history of interstitial lung disease, drug-induced pneumonitis, lung surgery, chest radiotherapy, performance status, oxygen supplementation, and traction bronchiectasis on computed tomography (CT) at diagnosis as explanatory variables. Results: A total of 129 patients experienced drug-induced pneumonitis in the study period. The median age (range) was 72 years (25–86 years). There were 60 men (69.8%) and 39 women (30.2%). The number of patients with lung cancer, breast cancer, biliary tract and pancreatic cancer, upper gastrointestinal tract cancer, lower gastrointestinal tract cancer, melanoma, and other cancers were 70, 11, 11, 10, 9, 8, 10, respectively. According to the clinician, drug-induced pneumonitis was induced by immune-checkpoint inhibitors (ICI), molecular targeted agents (TKI), and cytotoxic agents (CTX) in 26, 22, 81 patients, respectively. Among patients with drug-induced pneumonitis requiring hospitalization, a total of 15 (11.6%) patients (ICIs: 2 [7.6%]; TKIs: 1 [4.5%]; CTX: 12 [14.8%]) died because of drug-induced pneumonitis. A logistic regression analysis revealed a history of chest radiotherapy and lung surgery, poor performance status, and traction bronchiectasis on CT at diagnosis as the independent risk factors for mortality in drug-induced pneumonitis requiring hospitalization. Conclusions: The mortality rate of drug-induced pneumonitis requiring hospitalization was 11.6% and tended to vary with the antineoplastic agent. In patients hospitalized because of drug-induced pneumonitis, history of lung surgery and chest radiotherapy and traction bronchiectasis on CT indicated poor prognosis. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: H. Horinouchi: Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): BMS; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): MSD; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Chugai; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Taiho; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): AstraZeneca; Research grant / Funding (self), Research grant / Funding (institution): Astellas; Research grant / Funding (self), Research grant / Funding (institution): Merck Serono; Research grant / Funding (self), Research grant / Funding (institution): Genomic Health; Honoraria (self): Lilly. K. Tamura: Research grant / Funding (self), Research grant / Funding (institution): Pfizer; Research grant / Funding (self), Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (self), Research grant / Funding (institution): MSD; Research grant / Funding (self), Research grant / Funding (institution): Eli Lilly; Research grant / Funding (self), Research grant / Funding (institution): Eisai; Research grant / Funding (self), Research grant / Funding (institution): Cyugai; Research grant / Funding (self), Research grant / Funding (institution): Ono. T. Okusaka: Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Novartis Pharma K.K.; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Ono Pharmaceutical Co., Ltd.; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Eisai Co., Ltd.; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Eli Lilly Japan K.K; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): Taiho Pharmaceutical Co., Ltd.; Honoraria (self): Yakult Honsha Co., Ltd.; Honoraria (self): Teijin Pharma Ltd; Honoraria (self): Shire; Honoraria (self): AbbVie Inc; Honoraria (self), Advisory / Consultancy: Daiichi Sankyo Co., Ltd.; Honoraria (self): Takeda Pharmaceutical Co., Ltd.; Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): Dainippon Sumitomo Pharma Co., Ltd.; Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): Bristol-Myers Squibb. K.K.; Research grant / Funding (self), Research grant / Funding (institution): Pfizer Japan Inc.; Research grant / Funding (self), Research grant / Funding (institution): Kyowa Hakko Kirin Co., Ltd.; Research grant / Funding (self), Research grant / Funding (institution): AstraZeneca K.K.; Research grant / Funding (self), Research grant / Funding (institution): Chugai Pharmaceutical Co., Ltd.; Research grant / Funding (self), Research grant / Funding (institution): Nano Carrier Co., Ltd.; Research grant / Funding (self), Research grant / Funding (institution): Baxter. N. Boku: Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Taiho; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Ono; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Bristol Myers-Squibb; Honoraria (self): Chugai; Honoraria (self): Eli-Lilly. N. Yamazaki: Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): ONO Pharmaceuticals; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Bristol-Myers Squibb; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Novartis Pharma K.K.; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): MSD K.K.; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Merck Serono Co., Ltd.; Honoraria (self): Takeda Pharmaceutical Co., Ltd.; Honoraria (self): Chugai Pharmaceutical Co., Ltd.; Research grant / Funding (self), Research grant / Funding (institution): Takara-bio. Y. Ohe: Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): Chugai; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): ONO; Honoraria (self), Leadership role, Research grant / Funding (self), Research grant / Funding (institution): BMS; Advisory / Consultancy, Research grant / Funding (self), Research grant / Funding (institution): Kyorin; Advisory / Consultancy: Celltrion; Advisory / Consultancy: Amgen; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Lilly; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Bayer; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Pfizer; Honoraria (self): MSD; Honoraria (self), Research grant / Funding (self), Research grant / Funding (institution): Taiho; Research grant / Funding (self), Research grant / Funding (institution): Dainippon- Sumitomo; Research grant / Funding (self), Research grant / Funding (institution): Novartis; Research grant / Funding (self), Research grant / Funding (institution): Kissei; Research grant / Funding (self), Research grant / Funding (institution): Ignyta; Research grant / Funding (self), Research grant / Funding (institution): Takeda; Research grant / Funding (self), Research grant / Funding (institution): Kissei; Research grant / Funding (self), Research grant / Funding (institution): Daiichi-Sankyo. M. Kusumoto: Honoraria (self): Ono pharmaceutical Co. Ltd.; Honoraria (self): AstraZeneca K.K; Honoraria (self): MSD K.K; Research grant / Funding (self), Research grant / Funding (institution): Canon medical systems corporation. All other authors have declared no conflicts of interest.